ANALISIS PERILAKU KEUANGAN PADA PELAKU UMKM DI DESA PAGEDANGAN TANGERANG - Esa Mukti Aji, (2020)
This study aims to determine the effect of income and financial literacy on financial behavior in micro, small and medium enterprise in the village of Pagedangan, Tangerang Regency. The population in this study were all micro, small and medium enterprises in the Village of Pagedangan, amounting to 40 businesses." The "sample measurement using the non probability sampling method and saturation sample technique so the samples found were 40 respondents. The data collection is used through questionnaires. The analysis technique used is PLS (Partial Least Square) analysis method. The results of this study indicate that income and financial literacy have a significant effect on financial behavior.